Observation on Bird Fauna in Tiom, Jayawijaya, Irian Jaya - W Widodo (Department of Forest Resources Conservation and Ecotourism - IPB University, 1991)
An observation on birds in Tiom, especially in the Kenyam lowland-forest and the Bokon highlands, Jawawijaya, Irian Jaya was carried out in August to October 1990. Fourty one species were cencused and several of them were collected. Fifteen species of the birds are endemic. Its relative abundance and habitat, as well as their economic value, were discussed.